Recommendations for cyberbullying prevention and intervention: A Western Canadian perspective from key stakeholders - Hendry, Brittany P.; Hellsten, Laurie-ann Michelle; McIntyre, Laureen J.; Smith, Brenan R. R. (Frontiers in Psychology, 2023)
Introduction Cyberbullying, or repeatedly communicating antagonistic messages using digital or electronic media meant to deal out harm or discomfort to others, has been considered more pervasive and impactful than traditional bullying since perpetrators can remain anonymous online, are not bound by time or place. In addition, cyberbullied youth are reluctant to involve others such as an adult or confront the perpetrator adults. Therefore, the primary purpose of this study was to capture a holistic understanding of potential youth cyberbullying prevention and intervention strategies (i.e., inhibiting forces that may reduce cyberbullying) from key stakeholders with professional knowledge about cyberbullying (i.e., educational administration, psychological counseling, technology and bullying education consultation, policing, research, and social support services). Methods Twenty (n = 20) participants were recruited using purposive and snowball sampling techniques from both urban and rural school districts in one Western Canadian province to participate in either in a semi-structured individual interview (n = 16) or a scheduled focus group (n = 4) to achieve depth and understanding of cyberbullying issues. The I3 Model, a process-oriented metatheory of aggression with the potential to explain how cyberbullying behaviors continue to occur, was used as a frame to analyze the qualitatively gathered data using six phases of reflexive thematic analysis. Results Participants identified educational efforts related to awareness of cyberbullying and consequences of perpetration, digital citizenship programming for students and social skills training, providing remediation to youth who are in online conflict with one another, and parental engagement with the technology used by their youth as key factors in mitigating instances of cyberbullying. Discussion This study furthers research on cyberbullying prevention and intervention in schools by illuminating experiences from under researched and unique stakeholders in the field. These key findings and suggestions for future research are further discussed.